Soil carbon and nitrogen dynamics as affected by crop diversification and nitrogen fertilization under grain production systems in the Cerrado region - Sattolo, Thales Meinl Schmiedt (2020)
The agriculture has been largely responsible for soils C emissions mainly through land use change (LUC) from native vegetation (NV) to agrosystem. Despite that, Brazil is reference on soil (and crop) science and technology in agriculture towards sustainability and food security policies. The best example of the recent development of Brazilian agriculture was the transformation of Cerrado ecosystems from a non-fit agricultural land to a current major global breadbasket due to advanced management practices such as no-tillage, double cropping, proper fertilization and high-performance machinery. In this scenario of land use change (+ C emissions) and adoption of high-tech conservation agriculture (- C emissions) in Cerrado that long-term experiments were evaluated for: i) soil structure assessment through laboratory analyses and the visual evaluation of soil structure (VESS); ii) nutrient storage quantification through the soil C and N pools at depth, and iii) C dynamics understanding through modelling the decomposition kinetics of 14C-labelled substrates. The soil structure assessment reveled that the LUC from Cerrado to soybean and maize production systems (SMPS) negatively affected the soil structural quality and the physical properties, regardless of management practice and soil layer. Also, a slight decline in soil physical quality was detected (0-0.2 m) in SMPS related to the machinery operations required to manage a more diverse crop sequence. The VESS approach successfully identified changes in the soil structure induced by the soil use and management whereas laboratory analyses detected changes in specific functions associated to porosity and water dynamic. The quantification of soil C and N storage showed that the conversion from NV to SMPS lead to a soil C and N depletion stressed at 0-0.2 m layer for total stocks and down to 1.0 m for dissolved stocks. Although we had no differences on soil C and N for total stocks between SMPS treatments, the long-term mineralization assay indicates that the effects might be evident on field experiment further up. The C decomposition dynamics varied mostly within layers, substrates and priming than site, agroecosystems, and nutrient availability. On average, higher C use efficiency (CUE) were found under SMPS, subsoils samples and cellulose application as response of soil microbial community. Priming demonstrated that the initial lag-phase on decomposition kinetics of subsoils were probably related to dormant microorganisms instead of minor microbial biomass and low nutrient availability in Oxisols. Overall, the conversion from NV to SMPS promotes depletion of soil functions (i.e., physical structure, stocks, and nutrient cycling). On the other hand, the soybean-maize succession is a successful grain production system providing two harvesting every year while holding the soil C and N stocks suitable for SMPS. Ultimately, the SMPS in Cerrado have great potential for C stabilization mostly in subsoil.